Does Soil Testing for Fertiliser Recommendation Fall Short of a Soil Health Card? - Raj Gupta; R. N. Sahoo; Inder Abrol (Journal of Agronomy Research, 2019)
Nutrient depletion and imbalanced use of fertiliser nutrients, inappropriate tillage and rain- water management practices often result in land degradation. Declining soil health contributes to climate change through loss in soil productivity, biodiversity, soil carbon, and moisture and ecosystem services. In order to address declining soil health, government of India has launched a soil health card (SHC) scheme aimed at need base use of chemical fertilisers. The paper points out the short-comings in the SHC scheme. Balanced and need base use of chemical fertilizers can be helpful in environmental protection and restoring soil health. The paper identifies potential agronomic practices and production management systems that can reduce our dependence on synthetic nutrients. Integration of soil fertility management domains with computer based QUEFT crop model has the potential of making fertiliser recommendations more domain and crop specific and less cumbersome. For soil health assessment chemical indicators must be integrated with physical and biological properties of the soils which can be predicted through reflectance spectroscopy. For assessing soil health related issues across different agro-ecoregions, there is however an urgent need for building-up more robust soil reflectance libraries.
Keywords: Soil health card (SHC)